Corrigendum to "Undisturbed dust as a metric of long-term indoor insecticide exposure: Residential DDT contamination from indoor residual spraying and its association with serum levels in the VHEMBE cohort" [Environ. Int. 85C (2015) 163–167]. (September 2016) - Gaspar, Fraser W.; Chevrier, Jonathan; Bornman, Riana; Crause, Madelein; Obida, Muvhulawa; Barr, Dana Boyd; Bradman, Asa; Bouwman, Henk; Eskenazi, Brenda
Abstract: Although approximately 123 million people may be exposed to high levels of insecticides through the use of indoor residual spraying (IRS) for malaria control, few studies exist on indoor insecticide contamination due to IRS and its relationship with human exposure. In the present study, we developed a sampling method to collect undisturbed dust from 50 homes in Limpopo, South Africa, a region where dichlorodiphenyltrichloroethane (DDT) has been used in IRS programs to prevent malaria for 70 years. We quantified DDT and its degradation products, dichlorodiphenyldichloroethylene (DDE), and dichlorodiphenyldichloroethane (DDD) in dust samples to determine dust loading levels and compared these levels to paired serum concentrations of p, p ′-DDT and p, p ′-DDE in women residents. p, p ′-DDT and p, p ′-DDE had the highest detection frequencies in both dust (58% and 34% detection, respectively) and serum samples (100% detection). Significantly higher detection frequencies for o, p ′-DDT, p, p ′-DDE, and p, p ′-DDD were observed in dust samples collected in buildings that had been previously sprayed for malaria control. We also observed a significant, positive association between dust loading and serum concentrations of p, p ′-DDT and p, p ′-DDE (Spearman's rho = 0.68 and 0.54, respectively). Despite the low detection frequency in dust, our results indicate that undisturbed dust may be a good metric to quantify long-term home exposure to DDT-related compounds and that contamination of the home environment may be an important determinant/source of DDT and DDE exposure.